IN AND OUT OF LONDON D. H. Lawrence’s Nightmarish Experience (1914-1919) - Ceramella, Nick (Revista Leitura, 2021)
This article aims to analyse what is widely considered the hardest period in D. H. Lawrence’s life. We will look into the reasons why he rejected London’s intellectual circles, the city’s lifestyle, and its inhabitants. We will also see what spoilt his love at first sight with Cornwall, turning it into a hellish experience. In brief, we will focus on the long period (24 June 1914 – 14 November 1919) during which Lawrence and Frieda were forced to stay in England under difficult circumstances. Little wonder that those years, corresponding to the War period, became a nightmarish experience that would mark the rest of their lives.The resulting disappointment cast a shadow, especially on Lawrence, through all his life. What made things even worse in the long run was the disappointment deriving from the pollution which was already pestering the air there. Indeed, he was right since we have created a cloud of venomous fumes which keep hovering above us. The only solution, as Lawrence wisely and prophetically suggested, could be to connect back to nature and respect it, and certainly, nature will return the favour. In the meantime, unfortunately, it seems that we have not realised that our arrogant and disrespectful attitude has led us almost to the verge of self-destruction. However, surprising it may be, the shockingly violent and fast spreading Covid-19 pandemic, on forcing governments to impose lockdowns and stringent travelling restrictions even from country to country, has given nature a chance to be reborn and show itself in all its breathtaking beauty. Although we were mesmerized by that, let us not be under any illusion as we all know that it cannot last long because the world economy needs to get back to business as usual. Nonetheless, I believe it is high time that we took action to try to solve issues, such as global warming, all aspects of environmental pollution and its effects on ecosystems and human health. Let us face it, perhaps this is the last opportunity we have to save humanity from total destruction.